CHARACTERIZATION OF CANINE LEISHMANIASIS BY PCR-RFLP IN CUIABA, MATO GROSSO, BRAZIL - Almeida, Arleana do Bom Parto Ferreira; Paula, Daphine Ariadne Jesus de; Dutra, Valéria; Colodel, Edson Moleta; Nakazato, Luciano; Sousa, Valéria Régia Franco (Archives of Veterinary Science, 2012)
Leishmaniases are neglected zoonoses that are increasing in Brazil. The dog is considered the main reservoir of the visceral form in urban areas of Brazil and also important in maintaining the cycle of transmission of the cutaneous form in endemic areas. We used PCR-RFLP to identify the species of Leishmania involved in canine infection in Cuiaba City, Mato Grosso. Samples of bone marrow and lymph were collected from 181 dogs, of which 7.2% tested positive with indirect immunofluorescence and 24.9% using PCR-RFLP; a significant difference (p ≤ 0.05), had been possible to characterize the species Leishmania (L.) chagasi. This will aid in developing prevention measures and in the control of disease in Cuiaba and the surrounding area.